Biology of the Threatened Amaranthus pumilus Raf. and Amaranthus greggii S. Watson along Coastal Beach Fronts in North America - Stalter, Richard; Lonard, Robert I. (Journal of coastal research, 2025)
Stalter, R. and Lonard, R.I., 2025. Biology of the threatened Amaranthus pumilus Raf. and Amaranthus greggii S. Watson along coastal beach fronts in North America. Journal of Coastal Research, 41(1), 180–183. Charlotte (North Carolina), ISSN 0749-0208. The cosmopolitan genus Amaranthus is represented by 60 to 75 species in North America. Two species, Amaranthus pumilus and Amaranthus greggii, are restricted to sandy barrier island habitats in the Atlantic and Gulf of Mexico regions of North America. Amaranthus pumilus is a federally and globally threatened species. An opportunistic species that occurs under favorable strand conditions, A. pumilus disappears for extensive periods because of storms, erosion, or human disturbance. Typical habitat sites for A. pumilus are between the high tide mark and lower coppice foredunes and in overwash flats. Amaranthus greggii occurs on sandy barrier islands in the Gulf of Mexico from Louisiana to Texas and from Tamaulipas to the Yucatan peninsula in Mexico. Amaranthus greggii usually occurs above the mean high tide mark in the lee of flotsam to the margins of low foredunes, and it is subject to elimination by storm surges, erosion, and sand coverage.